In Vitro Antibacterial Activity of Prenylated Guanidine Alkaloids from Pterogyne nitens and Synthetic Analogues - Coqueiro, Aline [UNESP]; Regasini, Luis Octavio [UNESP]; Stapleton, Paul; Bolzani, Vanderlan da Silva [UNESP]; Gibbons, Simon (Amer Chemical Soc, 2014)
The present investigation deals with the antibiotic activity of eight natural guanidine alkaloids and two synthetic analogues against a variety of clinically relevant methicillin-resistant Staphylococcus aureus strains. Galegine (1) and pterogynidine (2) were the most potent compounds, with a minimum inhibitory concentration of 4 mg/L, to all tested strains. The preliminary chemical features correlating to anti-MRSA activity showed that the size of the side chain and the substitution pattern in the guanidine core played a key role in the antibacterial activity of the imino group. Guanidine alkaloids 1 and 2 are promising molecular models for further synthetic derivatives and, thus, for medicinal chemistry studies.